Vitreoretinal biomarkers of retinopathy of prematurity using handheld optical coherence tomography: a review - Kubsad, Deepika; Ohan, Masis A.; Wu, Jolan G.; Cabrera, Michelle T. (Frontiers in Pediatrics, 2023)
Retinopathy of prematurity (ROP) is caused by abnormal retinal vascularization in premature infants that has the potential for severe long-term vision impairment. Recent advancements in handheld optical coherence tomography (OCT) have enabled noninvasive, high-resolution, cross-sectional imaging of the infant eye at the bedside. The use of handheld OCT devices in the diagnosis of ROP in premature infants has furthered our understanding of disease state and progression. This review discusses the known and novel biomarkers of ROP severity in premature infants identified through handheld OCT and potential for future directions.